The Influence of In Vitro Gastrointestinal Digestion on the Anticancer Activity of Manuka Honey - Danila Cianciosi; Tamara Yuliett Forbes-Hernández; Sadia Afrin; Massimiliano Gasparrini; José L. Quiles; Emilio Gil; Stefano Bompadre; Jesus Simal-Gandara; Maurizio Battino; Francesca Giampieri (MDPI AG, 2020)
Manuka honey (MH) is a natural food with many beneficial properties to human health, thanks to its high variety of bioactive compounds; however, little is known about its bioaccessibility. The aim of this study was to evaluate and compare the polyphenol compounds, the antioxidant capacity and the anticancer activity of MH subjected to an in vitro gastrointestinal digestion in human HCT-116 colon cancer cells. Raw MH and digested MH (DMH) were assessed for total polyphenols and flavonoids by spectrophotometric and HPLC-ESI-MS/MS analysis, and total antioxidant capacity (TAC) using different methods. Cell viability, intracellular ROS production, apoptosis, cell cycle and colony formation capacity were tested after treatment with MH or DMH. Results showed that total polyphenols, total flavonoids and TAC were significantly (p < 0.05) reduced after in vitro digestion. In addition, MH and DMH at 8, 16 and 24 mg/mL had similar effects in inducing intracellular ROS production and in inhibiting the colon formation ability; MH induced a more marked apoptosis compared to DMH, while cell cycle was blocked in S phase by MH and in Sub G1 phase by DMH. Our results increase knowledge of the effect of gastrointestinal digestion on the biological effect of honey against colorectal cancer.